The Role of Social Media Hashtags in Political Promotions: Mediating Role of Supply Chain Communication - Achmad Jamil; Endi Rekarti; Rizki Briandana; Salsabilla Audinna (International Journal of Supply Chain Management, 2019)
The current study examines the impact of hashtags used in social media for political promotion and analyses the mediating role of supply chain communications (SCC) in the relationship. The current study was performed in Indonesia, where 301 Twitter users were surveyed about current variables with a questionnaire. The data was analysed through Statistical Product and Service Solutions (SPSS) and Analisis of Moment Structures (AMOS) in order to complete “structural equation modelling.” The findings of the current study depicted that increased social media hashtags about a political matter tend to increase significantly political promotion. Furthermore, it has been found that increased social media hashtags about a political matter significantly enhance the political communication in society. It means that increased hashtags enhance SCC, and SCC ultimately significantly enhances political promotion. The current study contributes to the literature and in practice, because it enhances the limited literature about the role of SCC in political promotion in association with social media hashtags. Practitioners should leverage the insights from hashtags to be the function as a promotion tool.